Are acceptance and commitment therapy-based interventions effective for reducing burnout in direct-care staff? A systematic review and meta-analysis - Reeve, Andy; Tickle, Anna; Moghaddam, Nima Golijani (Emerald, 2018)
Purpose: Work-related stress amongst staff working in direct care roles in mental health and intellectual disability settings is associated with a range of problematic outcomes. There has been a proliferation of research into the use of acceptance and commitment therapy (ACT)-based interventions in this staff population. The purpose of this paper is to review the extant literature. Design/methodology/approach: A systematic search of the literature was conducted, and seven studies identified which met the criteria for inclusion in the review, of which four were eligible for meta-analysis. Findings: Results of the meta-analysis were most convincing for the effectiveness of ACT-interventions to reduce psychological distress within a subgroup of those with higher distress at baseline. There was no statistically significant effect for the amelioration of burnout, nor for an increase in psychological flexibility (a key ACT construct). Research limitations/implications: Conceptual issues are considered including the purpose and treatment targets of ACT interventions, such as supporting valued living rather than diminishing stress per se. Methodological issues are discussed around the measurement of psychological flexibility. Originality/value: This review makes recommendations for future research and for the implementation of ACT-interventions for work-related stress in these settings.